Enchant the dawn - Ashley, Amanda ([Enchant, 2022)
When young vampire Dominic Falconer arrives in New Orleans, he comes to the rescue of Madison Bainbridge, and falling for this mortal beauty, soon discovers that they are surrounded by enemies, eager to use the stirrings of his heart to bring down his family.